Case report: Preimplantation genetic testing for infantile GM1 gangliosidosis - Zagaynova, Valeria A.; Nasykhova, Yulia A.; Tonyan, Ziravard N.; Danilova, Maria M.; Dvoynova, Natalya M.; Lazareva, Tatyana E.; Ivashchenko, Tatyana E.; Shabanova, Elena S.; Krikheli, Inna O.; Lesik, Elena A.; Bespalova, Olesya N.; Kogan, Igor Yu.; et al. (Frontiers in Genetics, 2024)
Ganglioside-monosialic acid (GM1) gangliosidosis (ICD-10: E75.1; OMIM: 230500, 230600, 230650) is a rare autosomal recessive hereditary disease, lysosomal storage disorder caused by mutations in the GLB1 gene that lead to the absence or insufficiency of β-galactosidase. In this study, we report a case of a Russian family with a history of GM1 gangliosidosis. The family had a child who, from the age of 6 months, experienced a gradual loss of developmental skills, marked by muscle flaccidity, psychomotor retardation, hepatosplenomegaly, and the onset of tonic seizures by the age of 8 months. Funduscopic examination revealed a «cherry red spot» in the macula, which is crucial for the diagnosis of lipid storage disorders. To find the pathogenic variants responsible for these clinical symptoms, the next-generation sequencing approach was used. The analysis revealed two variants in the heterozygous state: a frameshift variant c.699delG (rs1452318343, ClinVar ID 928700) in exon 6 and a missense variant c.809A>C (rs371546950, ClinVar ID 198727) in exon 8 of the GLB1 gene. The spouses were advised to plan the pregnancy with assisted reproductive technology (ART), followed by preimplantation genetic testing for monogenic disorder (PGT-M) on the embryos. Trophectoderm biopsy was performed on 8 out of 10 resulting embryos at the blastocyst stage. To perform PGT-M, we developed a novel testing system, allowing for direct analysis of disease-causing mutations, as well as haplotype analysis based on the study of polymorphic markers - short tandem repeats (STR), located upstream and downstream of the GLB1 gene. The results showed that four embryos were heterozygous carriers of pathogenic variants in the GLB1 gene (#1, 2, 5, 8). Two embryos had a compound heterozygous genotype (#3, 4), while the embryos #7 and 9 did not carry disease-causing alleles of the GLB1 gene. The embryo #7 without pathogenic variants was transferred after consideration of its morphology and growth rate. Prenatal diagnosis in the first trimester showed the absence of the variants analyzed in the GLB1 gene in the fetus. The pregnancy resulted in the delivery of a female infant who did not inherit the disease-causing variants in the GLB1 gene.